Tobacco extract in the control of the mealworm beetle in aviaries - Jacomini, Débora; Temponi, Lívia Godinho; Alves, Luis Francisco Angeli; Silva, Edson Antonio Alves da; Jorge, Tereza Cristina Marinho (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of tobacco extract on the control of the mealworm beetle [Alphitobius diaperinus (Coleoptera: Tenebrionidae)] in aviaries. The experiment was carried out in a completely randomized design, using four contact times (2½, 5, 7½, and 10 min) and four tobacco extract concentrations (0, 25, 50, and 75% dilution). The contact time and the dilution of the extract were independent; however, contact time had greater effect on insect mortality. The tobacco extract has insecticide potential in the management of aviaries, but toxicity tests should be performed on the birds.